Asymmetric Addition Reaction of Reformatsky Type Reagent to Nitrones: An Intermediate for Synthesis of Physiologically Active Substances - Deana Wahyuningrum (Jurnal Matematika & Sains, 2004)
Asymmetric addition reaction of Reformatsky type reagent, which was generated in situ from diethylzinc and iodoacetic ester, to carbon-nitrogen double bond in nitrones utilizing (R,R)-DIPT as a chiral auxiliary agent showed fairly moderate to high enantioselective products in fairly high chemical yields. Nitrones were known as one of potentially intermediate nitrogen-containing compounds for synthesizing/physiologically active substances, such as pharmaceutical and agrochemical substances. The best results of this type of reaction were achieved from the asymmetric addition to nitrone, 6,7-dimethoxy-3,4-dihydroisoquinoline N-oxide (73% ee) and N-phenyl-Î±-(dibenzylcarbamoyl)methanimine N-oxide (21% ee) with fairly high chemical yields. The use of additive in asymmetric addition reaction to 6,7-dimethoxy-3,4-dihydroisoquinoline N-oxide was found to be crucial in improving the enantioselectivity of reaction, since the best results mentioned were achieved in the presence of isoquinoline-N-oxide or pyridine-N-oxide (0.5 molar equivalent) as additive. The difference in stereo-structure between 6,7-dimethoxy-3,4-dihydroisoquinoline N-oxide and N-phenyl-Î±-(dibenzylcarbamoyl)methanimine N-oxide caused the effect of (R,R)-DIPT as chiral auxiliary agent, additives and slow charge addition method towards the course of reaction resulting different products with different enantioselectivity.